2017
DOI: 10.4172/2376-127x.1000325
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Demographic and Placental Risk Factors in Term Low Birth Weight in Ghana

Abstract: Background: Several studies report on factors that associate preterm birth and intrauterine growth restriction with low birth weight (LBW). However, few studies discuss risk factors that associate with LBW for full-term births. No such studies exist that involve a population from Ghana.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 39 publications
0
3
1
Order By: Relevance
“…3,4 However, extensive infarction and calcification was noted in the study conducted by Chandra p et al 24 All the gross placental measurements were significantly lower in LBW compared to controls in an univariate analysis. However, only the placental weight, and the largest and smallest distances from the point of insertion of the umbilical cord were highly associated with LBW in a stepwise logistic regression analysis done by Larysa et al 25 Microscopically, Intervillous fibrin was seen in 64% of placenta in our study. However in Bane et al study all the placenta showed intervillous fibrin.…”
Section: Resultscontrasting
confidence: 60%
“…3,4 However, extensive infarction and calcification was noted in the study conducted by Chandra p et al 24 All the gross placental measurements were significantly lower in LBW compared to controls in an univariate analysis. However, only the placental weight, and the largest and smallest distances from the point of insertion of the umbilical cord were highly associated with LBW in a stepwise logistic regression analysis done by Larysa et al 25 Microscopically, Intervillous fibrin was seen in 64% of placenta in our study. However in Bane et al study all the placenta showed intervillous fibrin.…”
Section: Resultscontrasting
confidence: 60%
“…The results for MUAC in our study are statistically non-significant. [9,10] Tobacco chewing, bidi smoking, and alcohol abuse is a practice that generally leads to risk to the fetus. Based on the maternal habits of these substance abusers the subjects were divided into consumers and non-consumers.…”
Section: Resultsmentioning
confidence: 99%
“…Maternal employment status is associated with LBW and stillbirth [15,20,21,[27][28][29][30]. Maternal unemployment [28,29] and labour work [30] increased the risk of LBW and stillbirths, whereas maternal employment was protective [15,21,27]. In some studies, occupation of the women could not be clearly defined as there could be combinations of occupations, for instance a housewife being unemployed, an entrepreneur or a peasant [18].…”
Section: Resultsmentioning
confidence: 99%
“…Some of the studies that showed no association between education level and placental disorders suggested that the mother may be educated but the health attendants may not have enough knowledge to detect complications resulting from placental disorders. Maternal employment status is associated with LBW and stillbirth [15,20,21,[27][28][29][30]. Maternal unemployment [28,29] and labour work [30] increased the risk of LBW and stillbirths, whereas maternal employment was protective [15,21,27].…”
Section: Social and Demographic Factors (Table 2)mentioning
confidence: 99%